Effect of distance feedback on pacing strategy and perceived exertion during cycling - Albertus, Y.; Tucker, R.; St. Clair Gibson, A.; Lambert, E. V.; Hampson, D. B.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of this study was to investigate whether providing incorrect distance feedback would alter pacing strategies, perceived exertion, and heart rate during 20-km cycling time trials (TT).